FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN MUSCULOSKELETAL DISORDERS (MSDs) PADA PEMANEN KELAPA SAWIT DI PT. JOHAN SENTOSA - Azzahri Isnaeni, Lira Mufti; Hastuti, Milda; Yusma, Renita Holbina (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The European Commission Supervisory Report calculates cases of MSDs causing 49.9% absence from work for more than three days and 60% permanent disability at work. While in Korea, MSD reduced a very high increase from 1,634 in 2001 to 5,502 in 2010. Musculoskeletal disorders (MSDs) are damage to muscles, nerves, tendons, ligaments, joints, cartilage or spinal discs. The purpose of this study was to study the factors associated with the occurrence of musculoskeletal disorders (MSDs) in oil palm harvesters at PT Johan Sentosa Bangkinang in 2019. This type of research is the type of this research is analytical research using cross sectional surveys. The population of this research was all 93 palm oil harvesters with 75 samples. The sampling technique uses simple random sampling. Data aids using a questionnaire. Data analysis in this study used univariate and bivariate analysis. The research results obtained from there is a significant relationship between Age and MSDs incidence p value 0,002 RP = 1,805 (95% CI: 1,224-2,661), there is a significant relationship between Work Periods and Event MSDs p value 0,001 Rp = 1,951 (CI: 95 %: 1,260-3,020), there is no relationship involving weight and height with the incidence of MSDs p value 0,314), there is a significant relationship between the Age of Oil Palm with the incidence of MSDs p value 0.001 RP = 1,944 (95% CI: 1,232-3,067 ) and there is a significant relationship between Land Contour and MSDs p value 0.003 RP = 1.738 (95% CI: 1.94-2.529). For PT. Johan Sentosa is expected to be able to provide knowledge about how to work really when harvesting so workers can avoid the MSD incident.